PENELUSURAN FUNGI ENDOFIT SEBAGAI PENGHASIL SENYAWA ANTIBIOTIKA DARI DAUN NANAS (Ananas comosus (L) Meer) - Fitriana Fitriana; St. Maryam; Tadjuddin Naid; Maryana Maryana (As-Syifaa Jurnal Farmasi, 2016)
A search endophytic fungi from the leaves of pineapple (Ananas comosus (L) Merr) as a producer of antibiotic compounds will be carried out in order to obtain the endophytic fungi that have the ability to produce bioactive compounds useful as antibiotics.. Results of endophytic fungi isolates obtained six fungal isolates (IJA 1, IJA 2, IJA 3, IJA 4, IJA IJA 5 and 6), which have a different macroscopic characterization of forms, edge and elevation colonies. Isolates pure microbial fermentation results in the test antibiotic activity against some bacteria using agar diffusion test. All isolates pure fermentation results showed inhibitory activity against all bacteria in test as Bacillus subtilis, Esherichia coli, Pseudomonas aeruginosa, Salmonella thypi, Shigella dysenteriae, Staphylococcus aureus, Streptococcus mutans, and Vibrio cholerae. The inhibition of fungi isolates shown in (IJA 4) with a 26 mm zone of inhibition against Esherichia coli bacteria.